Functional structure enhanced synergistic sensing from triboelectric–electromagnetic hybrid nanogenerator for self-powered rotating speed monitoring. (November 2022) - Mu, Jiliang; He, Huicheng; Song, Jinsha; He, Jian; Hou, Xiaojuan; Han, Xiaotao; Feng, Chengpeng; Zou, Jie; Yu, Junbin; Chou, Xiujian
Abstract: Abnormal motor speed caused by overload, eccentric load and bearing wear is one of the main fault manifestations of heavy-duty motor. On-line monitoring the speed in real time is of great significance for fault early warning and improving motor operating life. In this paper, a self-powered motor speed sensor based on a coaxial integrated triboelectric–electromagnetic hybrid nanogenerator is proposed. A modular magnet coupling is designed to synchronously transfer energy from the motor shaft to nanogenerator with opposite polarity magnet through non-mechanical contact, which is advantageous to reducing the noise interference induced by rigid connection. The nanogenerator structure is mainly composed of the rotator module including magnet and wear-resistant positive friction material of Polyamide-66 and the stator one fitted with carbon steel enhanced copper coil and negative friction material of PTFE. Especially, an innovative rotating lead structure consisting of a set of rolling and sliding metal balls is fabricated for the first time, which provides a unique solution for transmitting triboelectric charge on rotator. Moreover, the carbon steel column inset into coil hole increases the short-circuit current of electromagnetic generator by 35.2%. The electromagnetic current and triboelectric voltage are used to characterize motor speed in our design, and their sensitivity are 0.035 mA/rpm and 1.365 V/rpm in the range of 0-300 rpm, respectively. When they were conjointly analyzed, the linearity of sensor reaches 0.995, which is attractive and greatly enhances the accuracy using sensing signal to judge the abnormal state. Furthermore, maximum output power of the nanogenerator reaches 76.91 mW, which shows that the nanogenerator is Competent for self-powering the sensor and its controlling circuits. The experimentally results indicate that the proposed self-powered sensor provides a novel design concept for the measurement of rotation speed and exhibits immense potential in industrial detection and mechanical failure early warning. Graphical abstract: Highlights: Modular assembly design based on magnetic coupling drive reduces the noise interference induced by rigid connection. A rotating lead structure consisting of low-pair mechanism provides a solution for transmitting charge on rotator. The synergistic sensing properties of multiple detection signals increase the linearity of the sensor to 0.995. The embedding of carbon steel increases the short-circuit current of EMG by 35.2%. HSRS can realize accurate and real-time rotation speed monitoring of heavy-duty motor.